CROPPING PATTERN AND CROP RANKING OF MYSORE DISTRICT - Ningaraju; Das, S Arun (International Journal of Research -GRANTHAALAYAH, 2017)
With the limited resources of land and water in hand, their optimum use is a must to for increased production of food grains to the demands of increasing population. The productivity in any area can be substantially raised by growing the crops suitable to the area with the help of newly developed agricultural techniques. Rainfed crops would continue to dominate in the agriculture of Mysore district.